Chromium adsorption on coir pith charcoal from tannery wastewater (Bangladesh Journal of Scientific and Industrial Research, 2021)
Emission of high chrome tanning wastewater is catastrophic for the environment. In this work, the effectiveness of coir pith charcoal is stated for the removal of chromium from tannery wastewater. The charcoal yield from the coir pith was 2.4%. The prepared charcoal was characterized by Fourier transform infrared spectroscopy (FT-IR). The efficiency of coir pith charcoal for chromium removal was assessed experimenting with various parameters e.g., charcoal dose, contact time, and relative pH. The content of chromium in the raw wastewater and after treatment at filtrate was 3439.2 mg/L and 14.9 mg/L, individually. In the batch experiment at optimized condition, for 75 mL chrome wastewater at 4 g charcoal dose with 15 min contact time, the chromium removal efficiency was attained 99.6%. The level of chloride (Cl-), chemical oxygen demand (COD), and biochemical oxygen demand (BOD) were significantly reduced by 65.7%, 93.7%, and 95.6%, respectively. The use of coir pith charcoal could be an alternative source for the removal of chromium from chrome containing wastewater.Bangladesh J. Sci. Ind. Res.56(1), 53-60, 2021